The empress of salt and fortune - Vo, Nghi (A Tor.com Book, published by Tom Doherty Associates, 2020)
"A young royal from the far north, is sent south for a political marriage in an empire reminiscent of imperial China. Her brothers are dead, her armies and their war mammoths long defeated and caged behind their borders. Alone and sometimes reviled, she must choose her allies carefully. Rabbit, a handmaiden, sold by her parents to the palace for the lack of five baskets of dye, befriends the emperor's lonely new wife and gets more than she bargained for."--Provided by publisher.